Une École qui crée de l’Autre - Béatrice Mabilon-Bonfils; Virginie Martin (Recherches en Éducation)
In our political model, whose school was the cardinal, instrument, the Other must become the Same The republican school was built for the Common on an assimilationist mode. The presence of undervalued cultures, that is now of thinking as sustainable questions our citizenship and therefore our school. The historico-theoretical article aims to analyze social reversal process: a school, which is thought to the make the Common even if thise common is a product of social relations) is transformed into a school that creates another. It will be fed by empirical illustrations.